Hereditary gastric cancer Hereditäres Magenkarzinom - Wolf, E. M.; Geigl, J. B.; Svrcek, M.; Vieth, M.; Langner, C. (Pathologe, 2010)
Hereditary diffuse gastric cancer is an autosomal dominant cancer syndrome with approximately 70%-80% penetrance. The cumulative lifetime risk of clinically detected gastric cancer is 63%-83% for women and 40%-67% for men. The average age at diagnosis is 40 years. Approximately 25%-40% of patients carry a germline mutation of the CDH1 gene. This gene encodes the transmembrane protein E-cadherin which plays a central role in cell adhesion and signal transduction. Classified according to Laurén, patients develop multifocal diffuse signet-ring cell carcinoma and, in late stages, linitis plastica. In the foveolar neck region, the site of gastric stem cells, in situ signet-ring cell carcinoma has been identified as a precursor lesion of invasive cancer. Therein, pagetoid spread of tumour cells below the preserved epithelium within the basal membrane represents the characteristic morphology. PAS staining may facilitate detection of tiny lesions.The present article provides detailed information on this cancer syndrome from the point of view of the pathologist as well as the human geneticist, focussing on the multidisciplinary management of affected patients. © 2010 Springer-Verlag.
CRIS-Team Scopus Importer:2025-03-05
Keywords: E-cadherin; Familial gastric cancer; Hereditary diffuse gastric cancer; Histopathology; Molecular analysis